Optimasi Potensi Anti Escherichia coli dan Staphylococcus aureus Kombinasi Ekstrak Etil Asetat Allium cepa dan Allium sativum - Suprianto; Dikari Harita; Dwi Setio Purnomo (Jurnal Indah Sains dan Klinis, 2023)
Background: Natural antibiotics are often used as an alternative therapy. Microbial infections are the main cause of mortality and morbidity in developing countries, including Indonesia. Staphylococcus aureus and Escherichia coli are two microbes that are often used for testing natural antibiotics. Objective: This study aims to optimize the combination of shallot and white onion extracts to potentially inhibit bacterial growth and development. Method: This study used a randomised design method of a combination of onion and garlic extracts tested based on the inhibitory area response. Results: The combination of shallot and white onion ethyl acetate extracts showed activity as an inhibitor of bacterial growth and development. The combination of EBM and EBP provides an inhibitory response against Escherichia coli (X2) and Staphylococcus aureus (X3). Conclusion: Combining EBM and EBP can inhibit the growth and development of Escherichia coli and Staphylococcus aureus. The best combination as an inhibitor of growth and development was Escherichia coli (X2; 14.53 mm) and Staphylococcus aures (X3: 15.7 mm), respectively